2022
DOI: 10.3390/su14137996
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Plant-Based Milk Alternatives Part 1: Composition, Sensory, and Nutritional Value

Abstract: Consumers are becoming increasingly interested in reducing the consumption of animal-based foods for health, sustainability, and ethical reasons. The food industry is developing products from plant-based ingredients that mimic animal-based foods’ nutritional and sensory characteristics. In this study, the focus is on plant-based milk alternatives (PBMAs). A potential problem with plant-based diets is the deficiency of important micronutrients, such as vitamin B12, B2, and calcium. Therefore, an analysis of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…The protein content was not significantly different from each other. The oat milk obtained by our process can provide around 1% of protein ( Table 5 ), which is comparable to or higher than previously reported commercial products (0.3–1.0% of protein) [ 38 ]. Moreover, it is not significantly different from the commercial product analyzed in the present study ( Table 5 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The protein content was not significantly different from each other. The oat milk obtained by our process can provide around 1% of protein ( Table 5 ), which is comparable to or higher than previously reported commercial products (0.3–1.0% of protein) [ 38 ]. Moreover, it is not significantly different from the commercial product analyzed in the present study ( Table 5 ).…”
Section: Resultssupporting
confidence: 81%
“…The lipid content was different among samples, which could be due to differences in the raw materials. The lipid content of oat milk produced from ZBY01, ZBY09, and AO was significantly higher, whereas the lipid content of the oat milk produced from ZZH02 was comparable to that of the commercial product and previously reported oat milk [ 38 ]. The oat milk samples and commercial product can provide around 60–73 mg/mL of carbohydrates, which is comparable to previous reports [ 38 ].…”
Section: Resultsmentioning
confidence: 52%
“…However, the mean of our data obscures that two of the almond PBMA brands contained ∼210 mg/100 g, while the third brand contained 43.1 mg/100 g (Figure ). Samples from studies done in Germany, Greece, New Zealand, Spain, and Turkey have typically found the calcium content in PBMAs in the range of 30–70 mg calcium/100 g, but some have reported values as high as 100 mg/100 g. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ESU World food LCA database (October 2019) was used for oat drink, conventional and organic soy drink, almond drink, and conventional and organic milk. Fortified PBMAs differ largely in their additives (Pointke et al) [38]. Taking into account these differences, only data sets from unfortified PBMAs with similar percentages of plant-based raw material were used (Table 2).…”
Section: Databasesmentioning
confidence: 99%
“…Both PBMAs and milk beverages differ in their nutritional composition, as shown by Pointke et al [38]. Accordingly, LCA results were expressed and related to the major dietary components: contents of energy (kcal) and protein (g) of the beverages.…”
Section: Life Cycle Assessment Nutritional Value-indexmentioning
confidence: 99%